A novel device with 36 channels for imaging and signal acquisition of the gastrointestinal tract based on AC biosusceptometry - Paixao, Fabiano C.; Quini, Caio C. [UNESP]; Baffa, Oswaldo; Miranda, Jose Ricardo de A. [UNESP]; IEEE (Ieee, 2010)
The alternate current biosusceptometry (ACB) is a biomagnetic technique used to study some physiological parameters associated with gastrointestinal (GI) tract. For this purpose it applies an AC magnetic field and measures the response originating from magnetic marks or tracers. This paper presents an equipment based on the ACB which uses anisotropic magnetoresistive (AMR) sensors and an inexpensive electronic support. The ACB-AMR developed consists of a square array of 6x6 sensors arranged in a first-order gradiometer configuration with one reference sensor. The equipment was applied to capture magnetic images of different phantoms and to acquire gastric contraction activity of healthy rats. The results show a reasonable sensitivity and spatial-temporal resolution, so that it may be applied for imaging of phantoms and signal acquisition of the GI tract of small animals.